Strategy for Knowledge Management Sustainability: A Lesson from The Industrial Automation Unit - Adi, Dian Purnomo; Fahmi, Idqan; Najib, Mukhamad (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Organizational knowledge is a combination of individual’s knowledge within the organization. Specialize individual knowledge is developed inside the organization. Therefore, it should belong to the organization and be stored in the organization. The Industrial Automation (IA) department implements simple knowledge management (KM) in the form of a web blog. However, the KM implementation becomes inconsistent. This inconsistency can lead to knowledge loss and knowledge gaps if there are individual changes within the organization. This study aims to analyze the condition of the IA department’s KM, analyze the factors that affect the sustainability of IA’s KM and formulate strategies for the sustainability of IA’s KM. The analysis of KM is carried out with the following factors: culture, training and development, reward, performance system, and technology. Supervisor’s order is still something that can help to build the knowledge-sharing habit. Employees do not get training regularly. Employees feel that they have not received good appreciation for the knowledge sharing and have not been included in the performance appraisal. Technology has been well adopted in KM. SEM-PLS analysis shows that training and development is a significant factor of KM sustainability. SEM-PLS result and content analysis construct managerial implication and KM sustainability strategies formula: develop a yearly training plan, establish problem-solving forum, and improving KMS implementation. Keywords: content analysis, knowledge management, SEM-PLS, sustainability, training